Performance analysis of a thermoelectric air duct system for energy-efficient buildings - Irshad, K. (Elsevier Ltd, 2015)
This paper describes experimental and simulation study results of an air duct system that cools down airflow by using TEMs (thermoelectric modules). This system is designated as TE-AD (thermoelectric air duct) system which consists of twenty four TEMs along with heat sink and fan for circulation of air. Both experimental and simulation results were in good agreement with each other and showed that the TE-AD system reduces room temperature in the range of 1.2-5.3 Â°C and humidity in the range of 5-31. The COP (coefficient of performance) of the system ranges from 0.392 to 0.679 under different operating input current for Malaysian weather conditions. By comparing TE-AD system with conventional air conditioning system, energy saving of 38.83 and CO2 emission mitigation of 38.81 was achieved with additional benefits of high reliability and refrigerant free system. Â© 2015 Elsevier Ltd.